Podobe slovenskega podjetništva v letu 2006 - Tajnikar, Maks; Tominc, Polona; Duh, Mojca; Širec, Karin; Pušnik, Ksenja; Bradač Hojnik, Barbara; Rus, Matej (University of Maribor Press, 2007)
Images of Slovenian Entrepreneurship in 2006. In the first part, we investigated existing gaps of entrepreneurial activity relating to personal characteristics and gender of entrepreneurs in Slovenia on a sample of Slovenian small and medium-sized enterprises. We divided personal characteristics of entrepreneurs into psychological and non-psychological motivational factors. The second part deals with the absorption capacity of the results of research and development and converting them into innovative products of small and medium-sized enterprises. In the third part, we studied the factors for failure and the success of growing companies. In the fourth part, we studied the behaviour of family businesses in the early stages of the entrepreneurial process. In the fifth part, we discussed the standardization process, which takes place at European Union level, the importance of cooperation in this process for small and medium-sized enterprises and the importance of implementing standards. We also discussed about the role of a supportive environment, which operates in the form of public and private organizations at both the national level and at the level of the European Union. In the sixth section, we provided the basic features of Slovenian companies in 2005.